Identifying the Challenges in Commercializing High Technology: A Case Study of Quantum Key Distribution Technology - Anas Al Natsheh; Saheed A. Gbadegeshin; Antti Rimpiläinen; Irna Imamovic-Tokalic; Andrea Zambrano (Talent First Network (Carleton University), 2022)
This article examines the challenges in commercializing high technologies successfully and sustainably using quantum key distribution (QKD) technology as a case study. Quantum communication is increasingly relevant to cybersecurity and nanotechnology, which will replace current technologies and change the way we live. To understand how such high technology could be successfully commercialized, we interviewed individuals from four metrology institutions and two international companies. The result revealed that scattered and small markets, supply chain development, technology validation/certification, a lack of available or adequate infrastructure, and after-sales services are the most serious challenges facing successful commercialization of quantum communication technology. To validate these challenges, we conducted a survey of 60 experts, 49 of whom agreed that above-mentioned factors could affect the commercialization success of QKD technology. Likewise, the survey revealed that technical development, customer orientation/awareness, and government regulations could also hinder the commercialization of QKD technology.